Asuhan Keperawatan Pada Tn. A Dengan Diagnosa Congestive Heart Failure (CHF) Di Ruang Igd Rumah Sakit Daerah Gunung Jati Kota Cirebon - Puspita Sari, Melati; Wahyuni, Uni; Nur Azmi, Nadila; Wulandari, Afni; Risdianto, Nugeraha (MEJORA Medical Journal Awatara, 2024)
Congestive Heart Failure (CHF) is a medical condition in which the heart is unable to pump enough blood to meet the oxygen and nutrient requirements of all body tissues. CHF risks deviations in basic human needs such as ineffective airway clearance, decreased cardiac output, hypervolemia, and others. Patients with CHF became the second largest cause of death in Indonesia in 2019 after stroke, with a doctor-diagnosed prevalence of 1.5% or 1,017,290 residents. The purpose of this case study is to provide nursing care to patients with a diagnosis of CHF. Using a qualitative approach with case studies as the main method, using observation sheets, interviews, and documentation studies. The case study took a patient as the subject of study, namely a patient with a diagnosis of CHF in the Emergency Room, Gunung Jati Hospital, Cirebon City. Nursing care management is based on meeting the needs of patients carried out in 1x5 hours. The results of the case study showed that after being given nursing care there was an increase in the effectiveness of airway clearance, increased cardiac output, and improved fluid balance. The conclusion is that nursing care is effective for CHF patients in meeting patient needs.